A rare case in an 11-year old child with bilateral primary orbital rhabdomyosarcoma with rapid onset of bilateral proptosis and temporal lobe abscess secondary to chronic suppurative otitis media - Gupta, Bikram K.; Tomar, Shubham (International Journal of Research in Medical Sciences, 2020)
A rare case in an 11-year old child with bilateral primary orbital rhabdomyosarcoma (RMS) with rapid onset of bilateral proptosis and temporal lobe abscess secondary to chronic suppurative otitis media (CSOM). This article describes the clinical, radiological, histopathological, and immunohistochemical findings. Orbital RMS is always unilateral and mainly presents as proptosis with lid edema and chemosis. The uniqueness of the present case is the simultaneous occurrence of bilateral RMS and temporal lobe abscess.